Financial stability reports in Latin America and the Caribbean - Cheng Hoon Lim; Alexander Klemm; Sumiko Ogawa; Marco Pani; Claudio Visconti (Journal of Banking and Financial Economics (JBFE), 2019)
Many countries in Latin America and the Caribbean now publish financial stability reports. They use FSRs as a tool for financial surveillance and communication. This study reviews their latest issues to assess their content, quality, and transparency, and the extent to which the country's macrofinancial and institutional context affect the quality of the publications. While some reports provide a strong analysis of risks and vulnerabilities, there are significant cross-country differences, and many reports could be improved by adopting a more comprehensive, forwardlooking, and thematic assessment of financial stability. A well thought out communication strategy, including a regular and predictable publication schedule and an easily accessible website, is also important to enhance the impact of the reports. Data gaps, particularly at the disaggregated level, are material and need to be urgently addressed.
Keywords: G01; G18; G28; 330; Financial Stability Report; Financial Supervision